The macroeconomic effects of re-applying the EU fiscal rules: Returning to the status quo ante or moving to expenditure rules? - Janis Jurgeleit; Lukas C. Oberhoff; Christoph Paetz; Sebastian Watzka (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
Against the background of the European Commission's reform plans of the Stability and Growth Pact (SGP) this policy brief uses the macroeconometric multi-country model NiGEM to simulate the macroeconomic implications of the most relevant reform options from 2024 onwards. Next to a return to the existing and unreformed rules based on achieving the so-called medium-term objective (MTO) for the structural balance and ensuring an adequate adjustment path towards this objective, the most prominent options include an expenditure rule linked to a debt anchor. Here we consider the proposals made by the European Fiscal Board (EFB) and the IMK (European Fiscal Board 2018, 2020; Dullien et al. 2020). Our results for the euro area and its four biggest economies, France, Italy, Germany, and Spain, indicate that returning to the existing rules of the SGP would lead to severe cuts to public spending. This holds particularly if the existing SGP rules were to be interpreted as they were in the past. A more flexible interpretation of the rules would only somewhat ease the fiscal adjustment burden. Introducing an expenditure rule along the lines of the EFB would, however, not necessarily and by itself alleviate the fiscal adjustment burden. Instead, our simulations show that great care must be taken to appropriately specify the expenditure rule, such that fiscal consolidation is achieved in a growth-friendly way. Raising the debt target to 90% and applying less demanding fiscal adjustments as proposed by the IMK would go a long way in achieving this goal. For the euro area, our results indicate that the additional yearly GDP of such a reform would correspond to around 0.5% of GDP in 2024, rising to 1.8% of GDP in the 2030s.
urn:nbn:de:101:1-2022110814181838831146
Keywords: 330; EU fiscal rules; Stability and growth pact; expenditure rule; Europäische Fiskalregeln; Stabilitäts- und Wachstumspakt; Ausgabenregel